Becoming a sexademic: Reflections on a 'dirty' research project. (September 2022) - Keene, Samantha
Sex and sexuality research can be understood as a form of 'dirty work', as despite its public need, it continues to be marginalised and demeaned within the academy and beyond. Through association, sex and sexuality researchers come to be labelled 'dirty workers' and are vulnerable to experiencing a range of stigmatised responses and negative repercussions. This article contributes to knowledge about the challenges involved in doing dirty work, through reflexively examining my experiences as a doctoral researcher investigating pornography's gendered influence. It explores the various institutional, professional and personal hurdles that I encountered during my dirty work journey and illustrates how these experiences may have been affected by my identity as a young, female researcher.